GEOLOGICAL CHARACTERISTICS AND GENESIS OF THE TUWU PORPHYRY COPPER DEPOSIT, HAMI, XINJIANG, CENTRAL ASIA - Han C.; Xiao W.; Yan Z.; Mao Q.; Zhao G.; Mao J.; Yang J.; Wang Z. (My University, 2006)
The Tuwu copper deposit, located in the Dananhu-Tousuquan island arc between the Kazakhstan-Junggar and Tarim plates, is one of the largest porphyry copper deposits in western China. Ore-hosting rocks consist of Early Carboniferous (333 ± 2 Ma) granodiorite- and plagiogranite-porphyries. Both the porphyries are elongate. The orebodies, consisting of veinlet-disseminated mineralization within the porphyries, grade range from 0.30% to 1.50% Cu. Mineralization can be assigned to six stages. Wall-rock alteration associated with the mineralization include silicification, chloritization, epidotization, sericitization and carbonatization. Three alteration zones have been recognized: phyllic zone, chlorite-biotite zone and propylitic zone. Re-Os dating indicates a 322.7 ± 3 Ma age for the deposit. δ34S values of the ore sulfides range from - 0.9‰ to + 1.3‰, with a mean of 0.11‰, reflecting a deep sulfur source. δ18O values of quartz in the ores range from 7.70‰ to 9.70‰, and the δ18O value of chlorite in the ores is 6.62‰. Calculated δ18Owater values of quartz and chlorite range from - 5.37‰ to + 6.62‰ and the δD values range from - 48‰ to - 63‰, suggesting that the ore fluids were mainly magma-derived in the early stage of mineralization. However, values for the late mineralization stage decrease, suggesting the addition of meteoric waters during the mineralization. Fluid inclusions within quartz grains are generally 3 to 30 μm in size, with gas proportions ranging from 5% to 60%, mostly from 10% to 15%. Homogenization temperatures of fluid inclusions are relatively low, bracketed between 101 and 409 °C, mostly between 100 and 200 °C. Salinities exhibit a wide range from 0.35 to 14.61 wt.% NaCl equiv., with a mean of 7.72 wt.% NaCl equiv., suggesting that ore fluids have low to moderate salinity. The ore-bearing plagiogranite porphyries show a strong depletion in heavy rare-earth elements, with average values of Yb and Y of 0.65 and 5.90 ppm, respectively, this being a characteristic geochemical signature for adakite. The geochemical signature of the adakites within the granitoid rocks represents a characteristic guide for further exploration for copper porphyry-type ore deposit in Eastern Tianshan. © 2005 Elsevier B.V. All rights reserved.
Keywords: FLUID INCLUSIONS; HYDROTHERMAL ALTERATION; ORE FLUID; PORPHYRY COPPER DEPOSIT; RADIOMETRIC AGE; TUWU, XINJIANG, CHINA; Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная